Egr1/p300/ACE signal mediates postnatal osteopenia in female rat offspring induced by prenatal ethanol exposure. (February 2020) - Wu, Zhixin; Pan, Zhengqi; Wen, Yinxian; Xiao, Hao; Shangguan, Yangfan; Wang, Hui; Chen, Liaobin
Abstract: Prenatal ethanol exposure induces developmental toxicities of multiple organs in offspring. Here, we investigate the effects of prenatal ethanol exposure on bone mass in postnatal offspring and explore its intrauterine programming mechanism. We found that prenatal ethanol exposure could induce bone dysplasia in fetuses and postnatal osteopenia in female offspring, accompanied by the sustained activation of the local renin-angiotensin systems (RAS) and inhibition of bone formation. Additionally, we also found that histone 3 lysine 9 acetylation (H3K9ac) and H3K27ac levels in the promoter region of angiotensin-converting enzyme (ACE) were increased in female offspring exposed to ethanol during pregnancy. In vitro, ethanol suppressed the formation of mineralized nodules and osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs), which was blocked by enalapril. Furthermore, ethanol promoted the expression and nuclear translocation of early growth response factor 1 (Egr1), which participated in the promotion of histone acetylation of ACE and subsequent RAS activation, by recruiting p300 and binding to the ACE promoter region directly. These findings indicate that the sustained activation of the local RAS might participate in bone dysplasia in fetus and postnatal osteopenia in the female offspring, while the Egr1/p300/ACE signal might be a key promoter of the sustained activation of the local RAS of the long bone. Graphical abstract: Image 1 Highlights: Prenatal ethanol exposure induces postnatal osteopenia in female offspring. Constant activation of RAS contributes to postnatal osteopenia in female offspring. Ethanol increases H3K9ac and H3K27ac levels of ACE via Egr1/p300 epigenetic mechanism.